Punakawan Sebagai Inspirasi Penciptaan Film Pendek Animasi Bertema Pendidikan Karakter - Arif Sulistiyono (Institut Seni Indonesia Yogyakarta, 2016)
Educational animation is an animated product produced specifically for the purpose of learning. Its popularity in helping students understand and remember information presented increased since the advent of computer graphics technology. The lack of an increase in the production of animated short films in Indonesia resulted in at least encountered the works of domestically-made animation education. Stimulation of creation of animated works based on the local culture should be a concern for creators to produce Indonesian animated film. This has encouraged the idea of research and the creation of the works to add alternative work spectacle for children to be more varied. The work produced will be expected to become one of the benchmarks for the creators of short animated films in Indonesia. The short animated film themed character education and have the characterization and design characteristics based on local wisdom is still a little bit. Production work is still dominated by elements that showed the humorous aspects of violence as like a common thing to do. It is extremely dangerous due to the development of the child's personality or character will indirectly entertained spectacle dominated by the less educated. Therefore bring back figures Punakawan as